Communication skill: A Challenge For Vocational High School Students in the 21st century - Fitriani, Somariah; Ilyas, Hamzah Puadi (Uhamka Press, 2019)
For vocational high school graduates to be accepted in business and industry, increasing the ability to use international languages, one of which is English is one of the main goals. Thus, the purpose of this community service is to train the students in understanding presentations appropriately. While the particular objectives are: 1) Improve the knowledge of strategies of writing and presentations in English well; 2) Enrich English vocabulary; 3) Improve writing and speaking skill; 4) Increase self-confidence, and 5) Prepare them to become professional graduates in terms of mastering English. There are thirty students of 12th grade of SMKN 56 North Jakarta participating in this training. The training was conducted within 12 hours, which was divided into three sessions for two days. At each meeting, students were monitored and practiced under the trainers’ guidance. The trainers also showed two examples of good presentations on YouTube. The training techniques are the lecture, discussion, brainstorming, and demonstration / direct practice that train students to understand every step by step in presentation and writing. The results show that students’ self-confidence developed, and vocabulary mastery, writing, and presentation skills increased as well. Out of 30 students, 5 participants delivered a presentation without reading the text. Although the results were not significant, the students had active participation in the discussion and practiced in groups and gave the speech in public. The evaluation result was 38.79 of a 1-4 scale with an excellent category. It is concluded that this training is highly needed and useful for vocational students.